The long polar fimbriae genes identified in Shiga toxin-producing Escherichia coli are present in other diarrheagenic E. coli and in the standard E. coli collection of reference (ECOR) strains - Toma, Claudia (2006)
Fil: Toma, Claudia. Division of Bacterial Pathogenesis, Department of Microbiology, Graduate School of Medicine, University of the Ryukyus, Nishihara, Okinawa; Japon.